EDUKASI GIZI ANEMIA PADA REMAJA PUTRI DI SMPN 1 SUGIHWARAS, BOJONEGORO - Firdaus, Desiana; Haliza, Alya Nur; Ismawati, Sevia; Sherllyantina, Shagitta Dwi; Hidayati, Elma Nur; Puspitasari, Widya (Jurnal Pengabdian Masyarakat, 2025)
Background: Anemia is a medical condition characterized by a lower than normal number of red blood cells or hemoglobin levels. In adolescent girls, anemia is caused not only by monthly menstruation but also by improper dietary patterns, particularly inadequate consumption of iron-rich foods. Micronutrient deficiencies such as anemia remain a prevalent issue in Indonesia. Recent national data indicate that the prevalence of anemia among adolescent girls in Indonesia is still around 32%, classifying it as a serious nutritional problem. Objective: This educational intervention aims to improve nutritional knowledge about anemia among adolescent girls at SMPN 1 Sugihwaras, Bojonegoro. Methods: This community service activity employed a lecture method to provide nutrition education about anemia to adolescent girls. The program was attended by 47 female students from grades 7 and 8. Prior to the education session, participants completed a pre-test questionnaire to assess baseline knowledge. Following the lecture, a question-and-answer discussion session was held. Finally, participants completed a post-test questionnaire before the session concluded. Results: The pre-test results showed that 19 students (40.4%) had a "good" category of nutritional knowledge, while the post-test results showed an increase to 43 students (91.4%) in the "good" category. The Wilcoxon Signed Rank test indicated a significant difference with a p-value < 0.05, demonstrating a significant improvement in nutritional knowledge among adolescent girls before and after the nutrition education. Conclusion: Nutrition education on anemia had a positive and significant effect. There was a significant increase in the average nutritional knowledge scores of adolescent girls following the educational intervention. Keywords: adolescent girls, anemia, nutrition education